2017
DOI: 10.1111/1365-2664.12963
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing plant diversity in a novel grassland using seed addition

Abstract: Abstract1. Restoration of novel ecosystems to a historical benchmark may not always be possible or advisable. Novel ecosystems may be managed by targeting specific components and accepting the novelty of other ecosystem attributes. The feasibility of this component-wise management of novel ecosystems has rarely been tested.2. In a novel grassland, where C 3 grasses have replaced C 4 grasses, nutrients have been elevated, and diversity has been lost due to a history of agricultural land use, we aimed to return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
0
16
1
Order By: Relevance
“…The removal of dominant grass species allows light availability for intertussock forbs [75,76], however, in their study in Australian grasslands Johnson et al found that seed limitation of forbs was a constraint to the recovery of degraded grasslands as indigenous forb recruitment mostly relied upon seed addition [76]. This finding is also supported by Zamin et al [77]. Another management strategy that could be employed in fragmented natural areas is the collection of forb seeds from nearby natural areas and sowing it in degraded urban open spaces including along road verges and railway embankments [78].…”
Section: Consequently How Will the Presence Of Time Lags And Potentimentioning
confidence: 78%
“…The removal of dominant grass species allows light availability for intertussock forbs [75,76], however, in their study in Australian grasslands Johnson et al found that seed limitation of forbs was a constraint to the recovery of degraded grasslands as indigenous forb recruitment mostly relied upon seed addition [76]. This finding is also supported by Zamin et al [77]. Another management strategy that could be employed in fragmented natural areas is the collection of forb seeds from nearby natural areas and sowing it in degraded urban open spaces including along road verges and railway embankments [78].…”
Section: Consequently How Will the Presence Of Time Lags And Potentimentioning
confidence: 78%
“…This is consistent with both the timing of natural and prescribed fires in the region, which typically occur in the cooler months following summer and studies which suggest that the interplay between fire, rainfall and temperature influences forb recruitment (Morris & Gibson‐Roy ; Zamin et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Although this theory has received criticism (Keeley & Pausas ), it does seem to be supported by some data which suggests that physical disturbance can promote recruitment of forbs in the absence of fire (Zamin et al . ). Responses to smoke but not heat shock may also be symptomatic of cooler burns which often take place in late‐autumn and winter where soil temperature may not exceed those used in this study (Morgan & Williams ).…”
Section: Discussionmentioning
confidence: 97%
“…If a grassland has a long history of grazing, it is likely that grazing-sensitive plant species have been lost from the system (Price et al 2010). Hence, reinstating fire or grazing removal is unlikely to recover those species without further management interventions such as seed addition and could lead to loss of species that require some disturbance (Kirkpatrick et al 2005;Johnson et al 2018;Zamin et al 2018). Little is known about the effects of native marsupial grazing on Australian temperate grasslands; a few studies have explored impacts of over abundant native animals, and high selectivity has been observed (Leonard et al 2010).…”
Section: Resource Variationmentioning
confidence: 99%